Tuesday
March 28, 2017

Post a New Question

Posted by on .

How do you do the problem 4k+7(-4-2k)=-2(k-2)
Please help me I keep trying and can't get the right answer thanks-steph

  • Geometry - ,

    if you're trying to find the value of k which satisfies the equation, just unwind the expressions.

    remove parentheses:
    4k+7(-4-2k)=-2(k-2)
    4k - 28 - 14k = -2k + 4

    Now combine terms:
    -10k - 28 = -2k + 4

    Now move all the "k" stuff to one side and the numbers to the other:
    -8k+2k = 4 + 28

    Combine terms again:
    -8k = 32

    Divide by the coefficient of k:

    k = -4

  • Geometry - ,

    Thank you so much

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question